2017
DOI: 10.7759/cureus.1410
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Anatomy of the Frenulum of the Oral Vestibule

Abstract: IntroductionThe frenula of the oral vestibule include the labial and buccal frenula. Abnormal labial and buccal frenula can affect facial esthetics and oral cavity function by retracting the gingival margin, creating a median diastema, and limiting lip movement. Because of the lack of information on these structures, we aimed to clarify their anatomy. MethodsA total of 34 sides from 17 fresh frozen cadaveric Caucasian heads were used in the present study. The specimens were derived from 11 male and 6 female ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 10 publications
0
18
0
3
Order By: Relevance
“…They correspond to the lateral border of the lower portion of the incisivus labii superioris fibers of the orbicularis oris muscle or the anterior border of the buccinator muscle. 32 As such, the buccal frenulum augments the role Upper lip tie is an inconsistently defined condition.…”
Section: Buccal Tiementioning
confidence: 99%
“…They correspond to the lateral border of the lower portion of the incisivus labii superioris fibers of the orbicularis oris muscle or the anterior border of the buccinator muscle. 32 As such, the buccal frenulum augments the role Upper lip tie is an inconsistently defined condition.…”
Section: Buccal Tiementioning
confidence: 99%
“…According to Gartner and Schein [ 11 ], a histological study of the labial frenulum demonstrated that muscle fibers and epithelial tissues exist deep to the labial frenulum, and they speculated those muscle fibers could be the cause of the unsuccessful outcome of the frenulectomy. Macroscopically, there is only taut connective tissue behind the labial frenulum [ 7 ]. The ILS is lateral to the connective tissue behind the upper frenulum and the MT lies lateral to the connective tissue behind the lower frenulum.…”
Section: Reviewmentioning
confidence: 99%
“…The buccal frenulum of the maxilla corresponds to the lateral border of the lower portion of the ILS and the anterior border of the buccinator. The buccal frenulum of the mandible corresponds to the lateral border of the upper portion of the MT and incisivus labii inferioris (ILI), and the anterior border of the buccinator [ 7 ]. In terms of periodontology, the buccal frenulum is considered one cause of gingival recession, and buccal frenulectomy of the high-positioned buccal frenulum might be indicated [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…The anterior border of the BM corresponds to the buccal frenulum (which means when the buccal membrane is retracted laterally) around the second premolar to the first molar region [ 4 ]. Also, the bony attachment of the BM corresponds to the mucogingival junction [ 5 ].…”
Section: Discussionmentioning
confidence: 99%